2011
DOI: 10.1002/jsfa.4463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of albusin B (a bacteriocin) of Ruminococcus albus 7 expressed by yeast on growth performance and intestinal absorption of broiler chickens-its potential role as an alternative to feed antibiotics

Abstract: Albusin B supplementation increased intestinal absorption and elevated the faecal Lactobacillus count, thereby promoting the growth performance of broiler chickens. These improvements resulting from albusin B supplementation provide evidence of potential alternatives to antibiotics in broiler chicken feed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…This suggests that multi-strain lactobacilli mixture composition might be a major concern in probiotic supplementation. The BA product applied in this study was a yeast with bacteriocin; it has been shown to be a broiler growth promoter owing to its ability to enhance the lactic acid bacteria growth in digestive tract and antibiotic activity [8]. In a broiler model, dietary supplementation with 0.15% to 0.3% S. cerevisiae resulted in a growth performance equal to that observed with antibiotic supplementation, and broiler chickens with yeast supplementation had better growth and carcass weight than control broilers [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that multi-strain lactobacilli mixture composition might be a major concern in probiotic supplementation. The BA product applied in this study was a yeast with bacteriocin; it has been shown to be a broiler growth promoter owing to its ability to enhance the lactic acid bacteria growth in digestive tract and antibiotic activity [8]. In a broiler model, dietary supplementation with 0.15% to 0.3% S. cerevisiae resulted in a growth performance equal to that observed with antibiotic supplementation, and broiler chickens with yeast supplementation had better growth and carcass weight than control broilers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cloning of the structural gene and plasmid construction for expression in S. cerevisiae and mass production of bacteriocin-expressing yeast were conducted as described by Wang et al [8]. The alb B gene (NCBI: AF469209) of albusin B from R. albus 7 was applied for expression in S. cerevisiae DBY 747 as a bacteriocin source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the factors affecting the production of albusin B by R. albus have been studied, much less regarding the mechanisms of action of these bacteriolysins is understood. Nonetheless, when recombinant Saccharomyces cerevisiae DBY 747 expressing albusin B of R. albus 7 was fed (at 2.5 g kg of body weight Ϫ1 ) to broiler chickens, an improvement of growth performance was observed, suggesting that ruminal bacteriocins could have a role as potential alternatives to the growth promoters used in livestock production (55).…”
Section: Discussionmentioning
confidence: 99%
“…Este gênero tem sido relacionado com a melhora na conversão alimentar, além da espécie Ruminococcus torques relacionada a melhora do desempenho das aves (TOROK et al, 2011;STANLEY, 2016). Estudo mostrou que a suplementação de dietas com bacteriocina produzida pelo Ruminococcus albus aumentou a absorção intestinal de nutrientes e elevou o número de Lactobacillus, diminuindo a população de bactérias patogênicas (WANG et al, 2011). Outro membro desta família é o gênero Anaerofilum, composto por bactérias anaeróbias que fermentam mono e dissacarídeos produzindo lactato, acetato e outros .…”
Section: Membros Da Família Staphylococcaceae E Ordem Bacillales Os unclassified